KAJIAN IN VITRO SUBTITUSI KONSENTRAT DENGAN PENGGUNAAN LIMBAH PERKEBUNAN SINGKONG YANG DISUPLEMENTASI KOBALT (Co) DAN SENG (Zn) DALAM RANSUM DOMBA - Iman Hernaman; Atun Budiman; Siti Nurachman; Kundrat Hidrajat (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
This research was aimed to investigate the effect of concentrate substitution with cassava plantation waste supplemented with cobalt and zinc in sheep ration. In vitro study was used in this experiment. Collected data were analyzed by Duncan’s test from Completely Randomized Design with four treatments and four replications. The experiment rations were R1 = 50% native grass + 50% concentrate, R2 = 50% native grass + 50% concentrate + 5 ppm cobalt + 30 ppm zinc, R3 = 50% native grass + 50% cassava plantation waste, R4 = 50% native grass + 50% cassava plantation waste + 5 ppm cobalt + 30 ppm zinc. The results showed that utilization of concentrate increased volatile fatty acid and N-NH3 concentration, and digestibility of dry and organic matter compared with cassava plantation waste. Volatile fatty acid and N-NH3 in sheep ration containing cassava plantation waste were still in normal range with dry and organic matter digestibility were up to 50%, but supplementation of cobalt and zinc had the same effect (P>0.05). It is concluded that cassava plantation waste can be used as sheep feed, but did not substitute concentrate. Supplementation of cobalt and zinc was not effective to improve fermentability and digestibility of cassava plantation waste.(Key words: Cassava plantation waste, Digestibility, In vitro, N-NH3, Sheep, Volatile fatty acid)